Affective Factors in Numeracy: Exploring How Math Anxiety and Self-Efficacy Influence Numeracy Skills - Nuraini, Ni Luh Sakinah; Permata, Santy Dinar; Cholifah, Puri Selfi; Aurelia, Davina; Nafisah, Nada; Afifah, Rifdah (SAINTIS Publishing, 2024)
This study investigates the relationships between math anxiety, self-efficacy, and numeracy skills among prospective primary school teachers at the State University of Malang. Through quantitative methods, data were gathered from 130 participants using structured questionnaires and numeracy tests. Descriptive statistics and correlation analyses were performed to assess the extent to which math anxiety and self-efficacy influence numeracy performance. The findings reveal weak yet statistically significant correlations, with math anxiety negatively affecting numeracy skills and self-efficacy showing a positive association. However, these variables together accounted for only 3.5% of the variance in numeracy performance, leaving 96.5% of potential predictors unexamined. This suggests that psychological factors like math anxiety and self-efficacy, while important, play a less direct role in shaping numeracy skills than traditionally assumed. The results underline the need for a broader and more integrative approach to understanding the multifaceted nature of mathematical competence. Future studies are encouraged to investigate additional contributing factors, such as cognitive and environmental influences, and to expand the sample size for broader generalization. These findings have implications for designing interventions that simultaneously address psychological and contextual elements to enhance numeracy skills among prospective educators.